Evaluation of some botanicals against citrus leafminer (Phyllocnistis citrella) and psylla (Diaphorina citri) on kagzilime (Citrus aurantifolia) - BORAD, P K; PATEL, M J; VAGHELA, N M; PATEL, B H; PATEL, M G; PATEL, BABUBHAI H; PATEL, J R (The Indian Journal of Agricultural Sciences, 2014)
A evaluation was conducted during 1997-99 at Anand on eight botanicals, viz mint (Mentha piperita L.), tulsi (Ocimum sanctum L.), ardusi (Adhatoda vasica L.), Karen (Nerium indicum M.), naffatia (Ipomoea fistulosa Mart), neem (Azadirachta indica A. Juss.), arni (Cierodendrum Bur.) and boufainvillea (Bougainvillea spp.) were evaluatedÂ  for their insecticidal property against-pests of kagzilime (Cirus aurantifolia S.), Spray of neen Phyllocnistis cirella St and psylla (Diaphorina citri K).